Pengaruh Terapi Kombinasi Aromaterapi dan Terapi Benson Terhadap Tingkat Fatigue pada Pasien Tuberkulosis Paru - Indah Sri Wahyuningsih; Dewi Pratiwi; Retno Setyawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Background: Fatigue is a common complaint experienced by patients with pulmonary tuberculosis during the course of treatment and may negatively affect physical functioning, psychological well-being, and overall quality of life. Inflammatory processes, side effects of anti-tuberculosis medications, and psychological factors are believed to contribute to the development of fatigue. Therefore, non-pharmacological interventions are needed as complementary therapies to help reduce fatigue levels in patients with pulmonary tuberculosis. Objective: This study aimed to determine the effect of a combination of aromatherapy and Benson relaxation therapy on fatigue levels in patients with pulmonary tuberculosis. Methods: This study employed a quasi-experimental design with a one-group pre-test and post-test approach. The sample consisted of 18 respondents selected using accidental sampling. Fatigue levels were measured using the Fatigue Assessment Scale (FAS). Data were analyzed using the Wilcoxon test because the data were not normally distributed. Results: The results showed a reduction in fatigue levels among patients with pulmonary tuberculosis after receiving the combination of aromatherapy and Benson relaxation therapy. Statistical analysis indicated a significant difference in fatigue levels before and after the intervention, with a p-value of 0.000 (p < 0.05). Conclusion:The combination of aromatherapy and Benson relaxation therapy had a significant effect on reducing fatigue levels in patients with pulmonary tuberculosis. This intervention may be recommended as a complementary therapy in nursing care for patients with pulmonary tuberculosis.